Improving water generator performance by using various evaporator pipe diameters - M. Mirmanto; M. Wirawan; I. Fathoni (Dinamika Teknik Mesin, 2026)
To overcome the problem of lack of drinking water during the dry season in certain areas, it is necessary to take advantage of technological advances, namely presenting a device to produce water called an air-water generator. However, the capabilities of this machine are still very varied and even very low, therefore it is necessary to conduct further research on this machine. This study aims to determine the influence of evaporator pipe diameter on the mass of water produced. This research was carried out experimentally using a cooling machine with a parallel evaporator made in the laboratory and the working fluid used was R134a refrigerant. The compressor used is a rotary type 0.5 PK compressor. The diameters varied were 1.00 mm, 2.00 mm and 3.00 mm. The results indicated that the highest water mass was 0.330 kg per hour obtained using a pipe diameter of 1.00 mm.Ã‚Â Meanwhile, the highest coefficient of performance (COP) was 7.34, obtained at a pipe diameter of 1.00 mm and the highest total heat transfer rate absorbed by the evaporator from the air occurred at a pipe diameter of 1.00 mm, which was 40.4 W.